Nature-inspired intelligent techniques for solving biomedical engineering problems - Kose, Utku 1985-; Guraksin, Gur Emre 1980-; Deperlioğlu, Ömer 1967- (IGI Global, Disseminator of Knowledge, 2018)
"This book provides a general view on applications of nature-inspired techniques (artificial intelligence) in biomedical engineering problems, discusses the potentials of the artificial intelligence field from this perspective, and finally improves awareness on the power of artificial intelligence and nature-inspired techniques on ensuring effective and efficient solutions for encountered biomedical engineering based problems" - .Provided by publisher
Includes bibliographical references and index
Keywords: Biomedical Engineering; Artificial Intelligence; Models, Biological; Bionics